Improving Learning Outcomes in Indian Primary Schools through Pedagogical Innovation - Hamid, Samia (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
India has demonstrated considerable progress in improving various aspects of its primary education system, including infrastructure and buildings, teacher student ratios, and school enrollment. However, student learning outcomes remain consistently low across the country. A review of the literature surrounding learning outcomes has highlighted gaps in school instruction and has shown the dire need for innovations in pedagogy and curriculum to improve student learning. Taking this into consideration, the present paper was written highlighting the few innovative pedagogical measures taken place around the nation to improve low learning outcomes.